2011
DOI: 10.1080/09544821003598573
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of ideas and concepts for creative stimuli in engineering design

Abstract: Creative idea generation is essential to novel concept development and ultimately innovation. The following paper describes an extensive industry-based study investigating the use of creative stimuli during a brainstorming session at the conceptual stages of design. A new approach to retrieving creative stimuli referred to as 'Sweeper' is proposed, which sources stimuli internal to a company's information repository. This creative stimuli tool is then compared to other creative stimuli tools using objective, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 26 publications
5
81
0
2
Order By: Relevance
“…A second set of studies then validated the utility of this specific task formulation by comparing students and practitioners engaged in this task and directly contrasting their activity with the above noted observation study from practice. This formulation of task type, ideation rules, and timing was further supported by comparison to prior works, such as, Howard et al's (2010) study of ideation in practice. As such, the task and outputs are both drawn from industrial context and have been explicitly baselined with respect to practice in multiple contexts (Cash et al, 2013).…”
Section: Methodsmentioning
confidence: 67%
“…A second set of studies then validated the utility of this specific task formulation by comparing students and practitioners engaged in this task and directly contrasting their activity with the above noted observation study from practice. This formulation of task type, ideation rules, and timing was further supported by comparison to prior works, such as, Howard et al's (2010) study of ideation in practice. As such, the task and outputs are both drawn from industrial context and have been explicitly baselined with respect to practice in multiple contexts (Cash et al, 2013).…”
Section: Methodsmentioning
confidence: 67%
“…Further effects of stimuli and contextual cueing (hinting at an area for a solution) were described by Liikkanen and Perttula (2007), showing that there is likely to be a notably greater number of ideas generated in the same (homogenous) category as the idea/stimulus being experienced. In previous research it has also been argued (Altshuller 1999) and shown (Howard et al 2010) that a case-based approach for retrieving stimuli can be of benefit. Nijstad et al (2002) performed a similar experiment to assess whether ideas proposed by other group members are stimulating or suppressing to an individual's creativity, though they only conducted the experiment using electronic representations of the group's ideas.…”
Section: Related Studiesmentioning
confidence: 99%
“…To retrieve the stimuli a mixture of approaches were used. Stimuli was either randomly retrieved (used in projects 1 and 3), or guided by using the TRIZ contradiction matrix/inventive principles (Altshuller 1999) used in project 2, or a newly developed Sweeper tool (Howard et al 2010) used in project 4. Sweeper proposes stimuli retrieved from previous projects by using a simple case-based design synthesis approach (Xu et al 2006) to match requirements of the previous projects with the current project.…”
Section: Types Of Stimulimentioning
confidence: 99%
“…For example, in literature is easy to find examples of TRIZ use in conjunction with the Axiomatic Design, either using the TRIZ from the perspective of Axiomatic Design as well as adapting the Axiomatic Design to the TRIZ frameworks [14,15]. The decomposition of issues in order to analyze the problems in their context and in relation to other factors is adopted in may areas of industrial production as well as in the more general problem solving matters [16].…”
Section: Discussionmentioning
confidence: 99%